Affective computing study of attention recognition for the 3D guide system. Issue 4 (14th July 2020) - Juang, Li‐Hong; Wu, Ming‐Ni; Lin, Cian‐Huei
Abstract : The eye‐tracking has been widely used in multiple discipline studies in recent years. However, most of the studies focused on the analysis for static images or text but less for highly interactive operation application. In addition, the affective computing rose and development in recent years have changed completely the design of thinking pattern for the human–computer interaction. Therefore, this study hopes to integrate the affective computing into the 3D guide system which was developed for the real campus through the eye‐tracking technology. The analysing user's gaze position and recognising attention emotion are according to the interest region which is stetted into the environment, and shows the feedback content corresponds to the area and the emotion. Through the most intuitive gaze analysis, the operation burden can be reduced and the user's interactive experience can be improved to achieve intuitive and user‐friendly experience. The results can also apply for medical therapy on human attention training.